FUNGICIDAL POTENTIAL OF ALLELOPATHIC WEED Cenchrus pennisetiformis ON GROWTH OF Fusarium oxysporum f. sp. lycopersici UNDER CHROMIUM STRESS - KHURSHID,S. (2016)
ABSTRACT The present study was conducted to assess antifungal potential of the allelopathic grass Cenchrus pennisetiformis Hochst. & Steud. against the fungal plant pathogen Fusarium oxysporum f. sp. lycopersici (cause of tomato wilt disease) under chromium stress. Laboratory experiments were performed in 10 mL volume glass test tubes each containing 1.0 mL of malt extract broth with seven concentrations (0, 50, 100, 150, 200, 250, 300 and 350 ppm) of each of Cr(III) and Cr(VI), and two concentrations (5% and 6%) of methanolic leaf, stem or root extract of C. pennisetiformis. A metal + weed extract amended medium was inoculated with the pathogen and incubated for 7 days at 25 C. Different concentrations of Cr(III) and Cr(VI) proved equally inhibitory resulting in 10-84% and 18-89% reduction in fungal biomass, respectively. Methanolic leaf, stem and root extracts of the weed reduced fungal biomass by 12-25%, 14-23% and 46-50%, respectively, over negative control. In combined application of methanolic extracts of different parts of C. pennisetiformis and metal solutions, root extract in combination with either Cr(III) or Cr(VI) showed the highest inhibitory potential against the fungus followed by leaf and stem extracts. In combination with methanolic root, leaf and stem extracts, different concentrations of Cr(III) and Cr(VI) significantly reduced fungal biomass by 54-99%, 14-99% and 9-95%, respectively, over negative control. Such studies have not been carried out previously. Results of the present investigation suggest that F. oxysporum oxysporum f. sp. lycopersici, the cause of Fusarium wilt disease in tomato, can be managed by application of extracts (or alternatively biomass) of C. pennisetiformis in chromium contaminated soils.